Penerapan Metode K-Means Clustering pada Data Jumlah Peserta Didik dan Jumlah Guru SMA Se-Bali - Yadhurani Dewi Amritha; Ni Putu Bintang Wirasti; Ni Made Ari Graciana Putri; Thea Felita (Departement of Mathematics Education, 2024)
A school allows children to play and enjoy their free time. Learning to count, read, and understand ethics and aesthetics are some of the free time activities. The resources and educational goals of a school determine the size and type of school. According to Law No. 14 of 2005, teachers are professional educators who are responsible for educating, guiding, training, assessing, and evaluating students in early childhood education, including primary and secondary education. This study will examine all public and private high schools in Bali with the 2023/2024 academic year, even semester with the formulation of the problem, namely how the application of the K-means Cluster method can be used on data on the number of students and teachers of high schools throughout Bali in grouping based on the number of high, balanced and low data for each number of students and teachers in high schools throughout Bali. In clustering or grouping teachers and students from 164 high schools throughout Bali. And from the 164 high school data, it is classified into 3 clustering. The result of this analysis is that there are 2 teacher and student data in cluster 1, namely, 50 teachers.